Schwann cell precursors represent a neural crest-like state with biased multipotency - Kastriti, Maria Eleni; Faure, Louis; Von Ahsen, Dorothea; Bouderlique, Thibault Gerald; Boström, Johan; Solovieva, Tatiana; Jackson, Cameron; Bronner, Marianne; Meijer, Dies; Hadjab, Saida; Lallemend, Francois; Erickson, Alek; et al. (The EMBO journal, 2022)
Schwann cell precursors (SCPs) are nerve-associated progenitors that can generate myelinating and non-myelinating Schwann cells but also are multipotent like the neural crest cells from which they originate. SCPs are omnipresent along outgrowing peripheral nerves throughout the body of vertebrate embryos. By using single-cell transcriptomics to generate a gene expression atlas of the entire neural crest lineage, we show that early SCPs and late migratory crest cells have similar transcriptional profiles characterised by a multipotent "hub" state containing cells biased towards traditional neural crest fates. SCPs keep diverging from the neural crest after being primed towards terminal Schwann cells and other fates, with different subtypes residing in distinct anatomical locations. Functional experiments using CRISPR-Cas9 loss-of-function further show that knockout of the common "hub" gene Sox8 causes defects in neural crest-derived cells along peripheral nerves by facilitating differentiation of SCPs towards sympathoadrenal fates. Finally, specific tumour populations found in melanoma, neurofibroma and neuroblastoma map to different stages of SCP/Schwann cell development. Overall, SCPs resemble migrating neural crest cells that maintain multipotency and become transcriptionally primed towards distinct lineages.
Keywords: buněčná diferenciace; Schwann cell precursors; Schwann cell lineage; crista neuralis; multipotency; regulons; Schwannovy buňky; neurogeneze; Cell Differentiation; periferní nervy; Neurogenesis; Peripheral Nerves; neural crest; Schwann Cells; Neural Crest